Ґенеза поняття "креативна компетентність" у контексті психолого-педагогічних досліджень - Дімітрова-Бурлаєнко, Світлана Дімова (Діса Плюс, 2017)
У статті розглянуто наукові погляди на визначення поняття "креативна компетентність". Проаналізовано основні підходи до розуміння суті креативності у сучасній науковій літературі. Автор зазначає, що креативність носить інтегративний характер, нерозривно пов'язана із інтелектуальною, емоційною, рефлексивною, вольовою, мотиваційною і діяльнісною сферами особистості. Автор простежує взаємозв'язок між поняттями "творчість" і "креативність" і робить висновок, що креативність і творче мислення як особистісні категорії є обов'язковим компонентом у складі професійної компетентності будь-якого фахівця. Виходячи з аналізу поняття креативної компетентності, стверджується, що вона включає в себе мотиви, цілі, ціннісні орієнтації, знання, вміння, навички. В кожному компоненті креативність виявляється на різних рівнях діяльності. Доведено, що креативна компетентність конкретизується автором як складне особистісне утворення, що охоплює сферу інтелекту, емоцій, моральних цінностей та уможливлює на принципово новому, інтегративному рівні перенесення набутих компетентностей з однієї галузі життєдіяльності в іншу з метою або досягнення принципово нового результату діяльності, або виконання діяльності на принципово новому якісному рівні. Підкреслено, що креативність не є вродженою характеристикою індивіда, а може бути сформованою завдяки особливим умовам виховання та навчання, основними з яких є розвиток особистості, мотивація до творчої діяльності та свобода індивідуальності.

The scientific approaches to the definition of the concept of "creative competence" are considered in the paper. Based on the analysis of the approaches to understanding the essence of creativity in modern scientific literature, the author divides them into three groups. In the first group, the cognitive nature of creativity such as the intellectual ability to form connections between different ideas, divergent thinking, intellectual activity, etc. is highlighted. According with the definition of creativity of the second group, the personal aspect of creativity is emphasized, and the attention is primarily focused in personal possibilities, personal potential and self-actualization of the individual. The third group consists of definitions, in which researchers rely on the social nature of creativity taking into account the influence of environmental factors on the formation, development and identification of creativity. The author notes that the creativity is integrative, and it is inseparably linked with intellectual, emotional, reflexive, volitional, motivational and active areas of interest of an individual. Also, the author traces the interrelation between the concepts of "oeuvre" and "creativity" and concludes that creativity and creative thinking, as personal categories are obligatory components in the composition of the professional competence of a specialist. Analysing the concept of creative competence, the author declares that it includes motives, goals, value orientations, knowledge and skills. In each component, creativity manifests itself at different levels of activity. The creative competence is specified by the author as a complex personal education that embraces the area of intellect, emotions, moral values and makes a transfer of acquired competences from a single branch of life to other its sides with a principally new, integrative level and with the goal of either achieving a fundamentally new result of activity or performing activities on a fundamentally new qualitative level. Moreover, the author points out that the creativity is not an innate characteristic of the individual, but it can be developed due to special conditions of upbringing and education, the main scopes of them are personality development, motivation for a creative activity and freedom of an individuality.
The genesis of the concept of "creative competence" in context of psychological and pedagogical research
Keywords: креативність; творчість; творчі здібності; творча діяльність; creativity; oeuvre; creative competence; creative activity